Expressive Voting and Irrational Outcomes in Corporate Elections - Tingle, Bryce (McGill Law Journal / Revue de droit de McGill, 2021)
Over the past three decades, shareholders have steadily been provided with greater voting power over corporate decisions. A great academic debate has arisen about the character and outcomes of the shareholder franchise. All parties to this debate start with the assumption that shareholders will vote rationally, and generally in their economic interests. There is a large empirical literature in political science, however, that finds that where the marginal value of a vote is low, information is processed and votes cast on the basis of strongly held prejudices, tribal loyalty, mood-affiliation, and a desire to flatter the voter’s self-image. In other words, the voter behaves irrationally from the standpoint of the real-world impact of their vote. This article reviews the empirical literature around shareholder voting to show that irrational voting characterizes the corporate franchise as well. Shareholders give their voting rights almost no value and their voting patterns do not reflect the economic performance of the company. Moreover, shareholders vote in ways that contradict their economic views (measured by looking at their trading decisions), and their voting is primarily driven by empirically questionable and deliberately ineffective corporate governance practices. Fortunately, the empirical political science literature provides some direction for reforming the corporate franchise.